Influence of Broiler Age on the Apparent Metabolizable Energy of Cereal Grains Determined Using the Substitution Method - Khalil MM; Abdollahi MR; Zaefarian F; Chrystal PV; Ravindran V (MDPI (Basel, Switzerland), 2022)
The present study investigated the influence of broiler age on the AMEn of wheat, sorghum, barley, and corn using the substitution method at six different ages (days 7, 14, 21, 28, 35, and 42). A corn-soybean meal basal diet was formulated and, the test diets were developed by replacing (w/w) 300 g/kg of the basal diet with wheat, sorghum, barley, or corn. Bird age influenced (p < 0.001) the AMEn of wheat and sorghum but had no effect (p > 0.05) on those of barley and corn. The AMEn of wheat increased with age (p < 0.001) from 12.53 MJ/kg DM in week 1 to 14.55 MJ/kg DM in week 2, then declined subsequently, but no linear or quadratic responses were observed. The AMEn of sorghum demonstrated a quadratic response (p < 0.05), increasing from 12.84 MJ/kg DM in week 1 to 13.95 MJ/kg DM in week 2, and then plateauing to week 6. Overall, the present results suggest that the effect of broiler age on the AMEn varies depending on the grain type. The current data suggest that the application of age-dependent AME or AMEn of wheat and sorghum will lead to more precise feed formulations.
Keywords: age; apparent metabolizable energy; broilers; grains; substitution